Acidity‐Triggered Transformable Polypeptide Self‐Assembly to Initiate Tumor‐Specific Biomineralization. Issue 15 (26th February 2023) - Liu, Yang; Jiang, Zhongyu; Tong, Shizheng; Sun, Yifu; Zhang, Yu; Zhang, Jiayuan; Zhao, Duoyi; Su, Yuanzhen; Ding, Jianxun; Chen, Xuesi
Abstract: Biomineralization is a normal physiological process that includes nucleation, crystal growth, phase transformation, and orientation evolution. Notably, artificially induced biomineralization in the tumor tissue has emerged as an unconventional yet promising modality for malignancy therapy. However, the modest ion‐chelating capabilities of carboxyl‐containing biomineralization initiators lead to a deficient blockade, thus compromising antitumor efficacy. Herein, a biomineralization‐inducing nanoparticle (BINP) is developed for blockade therapy of osteosarcoma. BINP is composed of dodecylamine‐poly((γ‐dodecyl‐l ‐glutamate)‐ co ‐(l ‐histidine))‐ block ‐poly(l ‐glutamate‐ graft ‐alendronate) and combines a cytomembrane‐insertion moiety, a tumor‐microenvironment (TME)‐responsive component, and an ion‐chelating motif. After intravenous injection into osteosarcoma‐bearing mice, BINP responds to the acidic TME to expose the dodecyl group on the surface of the expanded nanoparticles, facilitating their cytomembrane insertion. Subsequently, the protruding bisphosphonic acid group triggers continuous ion deposition to construct a mineralized barrier around the tumor, which blocks substance exchange between the tumor and surrounding normal tissues. The BINP‐mediated blockade therapy displays tumor inhibition rates of 59.3% and 52.1% for subcutaneous and orthotopic osteosarcomas, respectively, compared with the Control group. In addition, the suppression of osteoclasts by the alendronate moiety alleviates bone dissolution and further inhibits pulmonary metastases. Hence, the BINP‐initiated selective biomineralization provides a promising alternative for clinical osteosarcoma therapy. Abstract : A tumor‐microenvironment‐responsive transformable polypeptide nanoparticle is shown to initiate selective biomineralization for effective blockade therapy of osteosarcoma after activation by the acidic tumor microenvironment, which triggers continuous ion deposition to construct a mineralized barrier around the tumor and alleviates bone dissolution to suppress osteosarcoma progression, indicating significant potential for clinical osteosarcoma therapy.